Cross-sectional Analysis of Member Satisfaction Factors of KSPPS Mitra Usaha Ideal Jawa Timur - Afrizal Zulkarnaein; Taufiqur Rahman (LP2M IAIN Palopo, 2025)
This study aims to ascertain the relationship between the variables of service quality, trust, and ease of use on member satisfaction of KSPPS Mitra Usaha Ideal Jawa Timur. This is predicated on the idea that cooperative member satisfaction significantly impacts the cooperative's long-term success, with service quality, trust, and usability being elements thought to influence members positive experiences. This kind of study employs a cross-sectional design and is quantitative. Ninety-three participants made up the study's sample, which was gathered by distributing questionnaires. Instrument tests, multiple linear analysis tests, and classical assumption tests are the methods of data analysis that are employed. The findings indicated that while simplicity of use has no discernible impact on member satisfaction, service quality and trust do. The satisfaction of KSPPS Mitra Usaha Ideal Jawa Timur members is simultaneously impacted by the three independent variables. This study also shows a connection to disconfirmation theory, which compares expectations with performance, and negativity theory, which maintains that bad experiences affect a person more than positive ones.